Union with God: Cross Textual Reading in Surat Centhini VI and John 15: 1-8 - Antonius Galih Arga Wiwin Aryanto; Albertus Lilik Kurniawan (Studia Philosophica et Theologica, 2023)
The article wants to analyze the meaning of “union with God” in Javanese literature, Surat Centhini and in the Christian bible, John 15: 1-8. John Gospel has one focuses on the need of human beings to have a deep relationship with God. the same idea also can be found in Javanesse text, Surat Centhini. Both has the same purpose of spiritual life that is union with God or manunggaling kawula Gusti. The methodology will employ "cross-textual reading". The method seeks to provide space for readers to understand the text of the Holy Scriptures in the context of religious diversity, such as in Indonesia. The study wants to juxtapose the concept of manunggaling kawula Gusti which is taken from Serat Centhini VI, the song Gurisa pupuh 368:46-56 with the Gospel of John about the true vine. Hopefully this contextual theology effort will be able to contribute to theological reflection about relation between humans and God on the Javanese culture.